2018
DOI: 10.7458/spp20199112332
|View full text |Cite
|
Sign up to set email alerts
|

Implicados, intermitentes, desengajados? Estilos de mediação de pais de crianças de 3-8 anos que usam a internet

Abstract: Este artigo apresenta resultados do primeiro inquérito nacional sobre como crianças (3-8 anos) se relacionam com ecrãs em ambientes familiares, focando-se nas mediações de pais cujos filhos fazem uso da internet. Com base em literatura sobre o tema e em resultados sobre o contexto português, procedeu-se a análises estatísticas de correspondências múltiplas e de clusters que consideraram fatores do lado da criança e do lado dos pais relativamente a mediações ativas e de segurança. Da análise emergiram três tipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…This pattern coincides with the situation of children in India [14] and Portugal, as demonstrated by the data from Rocha and Nunes [32], which indicated exposure to 85 min of TV and 57 min of touchscreen use per day. Similar to the existing scientific evidence, this study's results reflected that TVs and touchscreens were identified as the most commonly used multimedia devices [11,27,33], demonstrating consistency in the types of devices to which children are exposed, regardless of cultural background [2,22].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This pattern coincides with the situation of children in India [14] and Portugal, as demonstrated by the data from Rocha and Nunes [32], which indicated exposure to 85 min of TV and 57 min of touchscreen use per day. Similar to the existing scientific evidence, this study's results reflected that TVs and touchscreens were identified as the most commonly used multimedia devices [11,27,33], demonstrating consistency in the types of devices to which children are exposed, regardless of cultural background [2,22].…”
Section: Discussionsupporting
confidence: 78%
“…In contrast to these guidelines, empirical studies on screen time have shown values above the suggested values [13,24,[26][27][28]. Early childhood sample studies have found that some children exceed 1 h of screen time starting at 18 months old, and that this time increases over subsequent years [2,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study conducted with younger children aged 3–8 years [ 25 ], researchers conducted face-to-face interviews in 656 Portuguese households. The study involved a questionnaire for the parents of children aged between 3 and 8 years and a separate questionnaire for children aged 6–8 years.…”
Section: The Multidimensional Use Of Sensors By Children and Youngste...mentioning
confidence: 99%
“…Concerning safety and privacy (Q8), 60.3% of the 10-12-year-olds have private profiles, as Figure 3 shows-research shows that this is often a condition imposed by parents when they allow children to first enter social media, and that parental monitoring is more common (Ponte et al 2017; Dias and Brito 2020), while 58.8% of the 13-16 year-olds have public profiles-research also shows that media literacy tends to grow along with age, and that older teenagers find it increasingly important to have more followers, and seek them actively (Ponte and Batista 2019).…”
Section: Practices Of Portuguese Tiktok Usersmentioning
confidence: 99%